Adult Learning in Community-Based Ecotourism - Pierre Walter (Adult Education Research Conference, 2010)
This paper examines the sites, processes and curriculum of adult learning in community-based ecotourism (CBE). It compares different forms of CBE; elaborates on community learning for capacity building, on the ecotourism curriculum, and on learning processes; and identifies areas in need of further research.